PELATIHAN SIKLUS AKUNTANSI DI PANTI ASUHAN ASIH LESTARI - Sugiarto D, Elizabeth; Oktavia, Elisa; Kristianto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
Asih Lestari Orphanage accommodates children who are sent to high school level, and from the information obtained, these children need tutors to strengthen and enrich the accounting cycle material to support their knowledge at school. Apart from that, accounting cycle training should be carried out from an early age so that when the orphanage children open a business in the future they can evaluate the performance of their business and make appropriate decisions. Asih Lestari (AL) Orphanage students need accounting cycle training based on invitation letter no.025/YPA.AL/SK/VIII/2023 from the leader of the AL orphanage. AL Orphanage students will be released into society (to become independent) after graduating from high school. Therefore, AL orphanage students need knowledge that can equip them to enter the business world. The aim of this PKM is to provide training in the accounting cycle to equip students if they later enter the business world. This PKM activity was carried out on Thursday 28 September 2023 at 08.00 – 13.00. This PKM is implemented with tutorials and evaluation through quizzes and questionnaires. This PKM mandatory output is presented at SERINA VII 2023, while the additional PKM output is in the form of an HKIkan Module.